THE INFLUENCE OF TEACHER COMMITMENT AND SCHOOL PRINCIPAL VISIONARY LEADERSHIP ON WORK CLIMATE - HASANAH, Tuti Robiatul; FETRIMEN, Fetrimen; SYARIF, Suryadi (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2023)
This research aims to examine the influence of the principal's commitment and visionary leadership on the work climate of State High Schools in Pesanggrahan District, South Jakarta. The method used is a quantitative method using a causal survey method with a path analysis approach. The population in this study was 218 public high school teachers in Pesanggrahan District, South Jakarta. The sample amounted to 141 using the formula developed by Slovin. Data analysis techniques using SPSS. The conclusions in this research are: 1) There is a positive and significant influence of Teacher Commitment on the Organizational Climate of Public High School teachers in Pesanggrahan District, South Jakarta, 2) There is a positive and significant influence of Visionary Leadership on the Organizational Climate of Public High School teachers in Pesanggrahan District, South Jakarta and 3) There is a positive and significant influence of Teacher Commitment on the Visionary Leadership of State High School Principals in Pesanggrahan District, South Jakarta. The implications of the research are that the aspects that need to be improved are: 1) Teacher commitment shows an influence on the organizational climate of state high school teachers in Pesanggrahan District, South Jakarta. 2) Visionary Leadership shows influence on the Organizational Climate of Public High School teachers in Pesanggrahan District, South Jakarta. It is important to improve Visionary Leadership by: 1) Direction setter, 2) Agent of change, 3) Spokesperson, and 4) Coach.